Dielectric and electrical properties of AgCrP2S6 and Cu0.2Ag0.8CrP2S6 layered crystals. (27th July 2017) - Zamaraite, I.; Dziaugys, A.; Banys, J.; Vysochanskii, Y.
ABSTRACT: The dielectric properties of newly synthesized AgCrP2 S6 and Cu0.2 Ag0.8 CrP2 S6 phosphorous chalcogenide crystals are presented. The measurements were performed in the frequency and temperature ranges 20 Hz to 1 MHz and 110 K to 470 K, respectively. No anomalies of complex dielectric permittivity indicating the polar phase transition can be detected in the measured temperature range. Dielectric spectra at high temperatures are mostly influenced by the electrical conductivity. From DC conductivity the activation energies have been calculated and compared with CuCrP2 S6 . The activation energies of the conductivity were found to be 1.26 eV and 0.75 eV for AgCrP2 S6 and Cu0.2 Ag0.8 CrP2 S6, respectively.